2008
DOI: 10.1186/1748-5908-3-39
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge transfer in Tehran University of Medical Sciences: an academic example of a developing country

Abstract: Background: In the past two decades, scientific publications in Iran have considerably increased their medical science content, and the number of articles published in ISI journals has doubled between 1997 and 2001. The aim of the present study was to determine how frequently knowledge transfer strategies were applied in Tehran University of Medical Sciences (TUMS). We were also interested in studying the determining factors leading to the type of strategy selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…Assessment of the status of research projects carried out at Tehran University during 2004 -2006 showed that the results of most projects (62%) were published in domestic journals (23), which is inconsistent with the present findings. The cause of discrepancy between the results is that researchers usually aim at publishing their findings from the beginning of the project (before research funding), while in case of residents' dissertations, students and professors may only consider them as part of the syllabus (23).…”
Section: Discussioncontrasting
confidence: 99%
“…Assessment of the status of research projects carried out at Tehran University during 2004 -2006 showed that the results of most projects (62%) were published in domestic journals (23), which is inconsistent with the present findings. The cause of discrepancy between the results is that researchers usually aim at publishing their findings from the beginning of the project (before research funding), while in case of residents' dissertations, students and professors may only consider them as part of the syllabus (23).…”
Section: Discussioncontrasting
confidence: 99%
“…One of the important aspects of a person's selfefficiency is how one person can have an effect on its own lifes' outcomes by having control (20). The concept of self-efficacy, which is the main factor in the theory of social learning, was first developed by Bandura's social psychology.…”
Section: Introductionmentioning
confidence: 99%
“…Policy transfer is intended to understand a process or set of processes in which different types of knowledge related to the institutions, programs, policies or systems in one governance sector or level are used to develop policies in another governance sector or level, like in the decentralization of DOT to the PHC service. [9][10] In João Pessoa-PB, Brazil, the policy transfer of DOT was done in 2007 to the PHC services. Formerly, the treatment was centralized at the Complexo Hospitalar de Doenças Infectocontagiosas Clementino Fraga, the referral unit (RU) in the state.…”
Section: Introductionmentioning
confidence: 99%